Penggunaan Jamu pada Pasien Hiperlipidemia Berdasarkan Data Rekam Medik, di Beberapa Fasilitas Pelayanan Kesehatan di Indonesia - Gitawati, Retno; Widowati, Lucie (Jurnal Kefarmasian Indonesia, 2015)
Hyperlipidemias are disorders which are manifested by elevation of blood lipid, such as total cholesterol and/or triglyceride above the normal level. Hyperlipidemia management is done by lifestyle modification (high-fiber diet, exercises) as well as using antidyslipidemias. On the other hand, non-conventional or traditional treatment of hyperlipidemias using herbals (jamu) is becoming ubiquitous, performed by jamu practitioner clinician (dokter praktik jamu). This study is a part of a web-site Jamu Registry Study, which is intended to figure herbal (jamu) dispensed by jamu practitioner clinician for hyperlipidemic patients. A descriptive, cross-sectional design is applied, using medical record data of ‘jamu’ patients from some health facilities, in 7 provinces in Indonesia. Results showed, out of 97 hyperlipidemic patients were mostly female (60.8%), aged 48-58 years (46.4%); most of them (62.9%) were treated merely with jamu for 1 – 2 weeks, and the rests were treated with jamu in combination with conventional and/or other alternative medication. The most jamu used were branded herbal capsules (55.7%) containing of Guazumae folium and Murrayae folium. Adverse events were reported in four cases i.e. diarrhea and diuresis